Digital twin and SHM informed risk based inspection planning for offshore wind turbine structures - Zhang, Wei-Heng; Wagner, Paul-Remo; Schubert, Matthias; Riber, Hans Jørgen; Faber, Michael Havbro; ICASP14; Bull, Thomas; Muff, Daniel Vig (My University, 2023)
Structural integrity management of wind turbine structures is typically based on equi-temporal inspection plans that do not account for the information that is or can be collected during their operation. This concerns the outcome of future inspections but also and very importantly the outcome of Structural Health Monitoring (SHM). Such information can be used within the framework of risk-based inspection (RBI) planning of structures to provide an information consistent basis for integrity management. In the present contribution we investigate how the concept of digital twins (DT) in conjunction with modern techniques of big data analysis may support this. The approach is demonstrated by a numerical example considering integrity management of a fatigue-sensitive detail of a 5MW reference offshore wind turbine support structure. The example results demonstrate the potential benefits of RBI planning and the value of taking into account the information from continuously collected SHM data.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED